Menelusuri Jejak Netizen: Dinamika Komunikasi dalam Respon Pelecehan Seksual di Media Sosial dan Implementasinya dalam Pendidikan Anak - Akhiruddin, Harris Rizki; Suhartono, Suhartono; Yuniseffendri, Yuniseffendri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Jember, 2024)
This research identifies five functions of speech acts in netizen comments on Instagram regarding the Brisia Jodie sexual harassment case. The declaration function is reflected in netizens' opinions, while the representation function can be seen from the reality expressed. Expressions of emotion show an expressive function, while advice to related parties reflects a directive function. Commitment to support or reject certain actions indicates a commissive function. The analysis also revealed four conversational implicatures. This research provides an in-depth understanding of netizens' responses to sensitive issues such as sexual harassment on social media, as well as the importance of ethical communication. The implications include developing an understanding of how netizens communicate on social media, designing more effective communication strategies, and increasing awareness of the importance of communicating responsibly. The results of this research provide valuable insight into netizens' communication behavior in responding to sensitive issues on social media. The implications of these findings can help in overcoming communication challenges in the context of sexual harassment cases and similar social issues in the future. Keywords : Implicature Analysis; Cultural Currents; Social Phenomenon; Netizens; Social media